Wound healing in cutaneous leishmaniasis: A double edged sword of IL-10 and TGF-β. (April 2017) - Abdoli, Amir; Maspi, Nahid; Ghaffarifar, Fatemeh
Highlights: IL-10 and TGF-β accelerate the physiological wound healing process. IL-10 and TGF-β control immunopathology caused by proinflammatory cytokines. IL-10 and TGF-β suppress immune responses in cutaneous leishmaniasis. IL-10 and TGF-β are responsible for parasite persistence in cutaneous leishmaniasis. Abstract: Immune responses have a crucial role during the wound healing process in cutaneous leishmaniasis (CL). However, there are several paradoxes in immunity against CL. On the one hand, regulatory cytokines interleukin (IL)-10 and transforming growth factor beta (TGF-β) increase susceptibility to CL through suppression of several proinflammatory cytokines that require for defense against CL. On the other hand, these cytokines play a pivotal role in the acceleration of wound healing process. This review discusses about the dual role of IL-10 and TGF-β during the wound healing process and immunity against CL to offer a new insight about wound healing in CL.